The determinants for the enzyme activity of human parvovirus B19 phospholipase A2 (PLA2) and its influence on cultured cells. - Xuefeng Deng (PLoS ONE, 2013)
Human parvovirus B19 (B19V) is the causative agent of erythema infectiosum in humans. B19 infection also causes severe disease manifestations, such as chronic anemia in immunocompromised patients, aplastic crisis in patients with a high turnover rate of red blood cells, and hydrops fetalis in pregnant women. Although a secreted phospholipase A2 (PLA2) motif has been identified in the unique region of the B19V minor capsid protein VP1(VP1u), the determinants for its enzyme activity and its influences on host cells are not well understood. The purpose of this study was to investigate the contribution of the PLA2 motif and other regions of the VP1u to the PLA2 activity, to determine the cellular localization of the VP1u protein, and to examine the effects of VP1u on cellular cytokines. We found that in addition to the critical conserved and non-conserved amino acids within the VP1u PLA2 motif, amino acid residues outside the VP1u PLA2 motif are also important for the PLA2 activity. VP1u and various mutants all revealed a nucleo-cytoplasmic distribution. UT7-Epo cells treated with prokaryotic expressed VP1u or mutant proteins with PLA2 activity released a large amount of free fatty acid (FFA), and the cell morphological change occurred dramatically. However, neither free fatty acid nor cell morphology change occurred for cells treated with the mutants without PLA2 activity. The wild type and the VP1u mutants with the PLA2 activity also activated TNF-α promoter and upregulated the transcription activity of NF-κB in transfected cells. In addition, we found that the amino acids outside the PLA2 domain are critical for the viral PLA2 activity, and that these tested VP1u mutants did not affect the localization of the VP1u protein.